2021
DOI: 10.12669/pjms.37.5.3773
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and assessment of Nutritional Status of school going children in rural areas of Islamabad

Abstract: Background and Objectives: Nutritional status is considered a significant and positive health indicator. It determines anthropometric measurements of preschool children, the height of children at the time of school entry and prevalence of low birth weight. The objective of the study was to determine the frequency of nutritional status and socio-demographic factors influencing under nutrition among school children of rural Islamabad. Methods: A cross-sectional study was conducted among school children of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…The current study found 9.2% children were overweight and 6%were obese. Results of a study done in Multan found that 10% of the studied population was overweight and 5% were obese 21 which is similar to our study results whereas in Farhin et al study which was done in a rural area, had found higher percentage of obese (12.8%) children than overweight (7.5% ) children 22 life style and consumption of junk food have been the leading causes 23,24 . According to Tanveer et al prevalence of overweight and obesity is more in boys than in girls of different districts of Punjab aged 5-19 years [25] whereas our study revealed that frequency of overweight was more in females (54.2%) whereas obesity was more common in males (74.2%) than females.…”
Section: Discussionsupporting
confidence: 89%
“…The current study found 9.2% children were overweight and 6%were obese. Results of a study done in Multan found that 10% of the studied population was overweight and 5% were obese 21 which is similar to our study results whereas in Farhin et al study which was done in a rural area, had found higher percentage of obese (12.8%) children than overweight (7.5% ) children 22 life style and consumption of junk food have been the leading causes 23,24 . According to Tanveer et al prevalence of overweight and obesity is more in boys than in girls of different districts of Punjab aged 5-19 years [25] whereas our study revealed that frequency of overweight was more in females (54.2%) whereas obesity was more common in males (74.2%) than females.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, the studies included reported that living in flood-prone areas [18], poor environments [26], and slum [36,57] were associated with higher malnutrition rates. Notwithstanding, living in either rural [28] or urban [28,44,58] environments or living in small houses [39] had a significant impact on malnutrition as well. Sanitation issues, such as unsafe drinking water [16,54] and poor personal hygiene [59] were also linked to malnutrition among in-school children and adolescents in developing countries.…”
Section: Nature Of Environment and Sanitationmentioning
confidence: 99%
“…Food safety will impact human health problems produced by a large food service company [1]. Malnutrition is a common public health problem [19]. Nutritious food can improve children's behavior [20].…”
Section: O5mentioning
confidence: 99%